New genus and new species of the tribe Augilini (Hemiptera, Fulgoromorpha: Caliscelidae) from Yunnan Province in China - Gong, Nian; Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2020)
New genus and new species of bamboo-feeding planthopper tribe Augilini, Neosymplana vittatum gen. et sp. n. is described from southwestern China. A key to Chinese genera of Augilini is given. The photos of the habitat of the species described are provided.